Didactic Principles of Optional Constructing Courses of Informatics Direction for Profile Studies - Yurii Doroshenko; Volodymyr Ocheretnyi (Pedagogical Discourse, 2016)
This publication presents and theoretically grounds didactic bases of optional constructing courses of informatics direction for profile studies in high school. To the latter belongs the current paradigm of education, adopted model of teaching, pedagogical approaches, didactic principles, factors and criteria, as well as the functional purpose of a certain optional course, which is manifested in the purpose (goals) of its teaching.For OCC (optional constructing courses) the structure of objectives is defined and it is found that the most viable is the integrative model of teaching, based on a combination of cultural, personality-oriented, developing and action- technological models.It is found out that profile education based on OCC should be realized on the basis of complex implementation of the following pedagogical approaches: person oriented, person-developing, semi-subjective (dialogical), environmental, information-semiotic, task, active, problem-active, competence, reflective, differentiated.The basic didactic principles and a number of specific principles are determined, specified and theoretically grounded. These principles complement each other and form a kind of system. According to the mentioned didactic principles of constructing OCC for profile studies the authors of the publication worked out the optional course «Fundamentals of computer graphics- information technologies. Algorithmization of graphic constructions», which received the stamp of MES of Ukraine and is implemented in profile education.Key words: didactic constructing, profile education, optional courses, teaching informatics technologies, educational process in high profile school optional course of informatics direction.